1996
DOI: 10.1200/jco.1996.14.6.1858
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, randomized comparative study of two doses of paclitaxel in patients with metastatic breast cancer.

Abstract: The results of this trial substantiate the activity of paclitaxel in the treatment of MBC. The observed superior efficacy with a dose of 175 mg/m2 over 135 mg/m2 suggests a dose-effect relationship. The clinical activity in anthracycline-resistant patients is particularly noteworthy. Paclitaxel in breast cancer needs further evaluation in large trials that use combination chemotherapy and involve earlier disease stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(152 citation statements)
references
References 10 publications
6
144
2
Order By: Relevance
“…ANC values should be interpreted in the context of this heavily pretreated population. This can be contrasted with the data of Nabholtz et al, 23 who reported Grade 3/4 neutropenia in 34% of first cycles using 175 mg/m 2 paclitaxel in patients with only 1 previous chemotherapy regimen. Given the finding that 9 of the 10 patients who had their dose escalated from 8 to 10 mg/m 2 per day in the second cycle tolerated this dose well, we recommend for Phase II studies that the dose of ixabepilone administered daily for 3 days every 21 days should be 8 -10 mg/m 2 per day on 3 consecutive days, starting with a dose of 8 mg/m 2 per day.…”
Section: Discussioncontrasting
confidence: 55%
“…ANC values should be interpreted in the context of this heavily pretreated population. This can be contrasted with the data of Nabholtz et al, 23 who reported Grade 3/4 neutropenia in 34% of first cycles using 175 mg/m 2 paclitaxel in patients with only 1 previous chemotherapy regimen. Given the finding that 9 of the 10 patients who had their dose escalated from 8 to 10 mg/m 2 per day in the second cycle tolerated this dose well, we recommend for Phase II studies that the dose of ixabepilone administered daily for 3 days every 21 days should be 8 -10 mg/m 2 per day on 3 consecutive days, starting with a dose of 8 mg/m 2 per day.…”
Section: Discussioncontrasting
confidence: 55%
“…[1][2][3][4][5][6][7] The effectiveness of paclitaxel in metastatic anthracycline-resistant breast cancer led to several large adjuvant clinical trials. The first of these to be reported, US Intergroup trial INT 0148 (CALGB 9344), demonstrated an improvement in diseasefree and overall survival from the addition of four cycles of paclitaxel to four cycles of cyclophosphamide and doxorubicin.…”
Section: Introductionmentioning
confidence: 99%
“…However, many patients receiving prolonged oncological treatment suffer from complications caused by adverse effects of these treatments. These patients may experience a poor quality of life and will often still relapse post-treatment (Goldfarb and Ben-Eliyahu, 2006;Nabholtz et al, 1996;Valero et al, 1995). The main reason current treatment options fail is thought to be due to cancer stem cells, which cannot be eradicated by traditional treatment modalities.…”
Section: Cancersmentioning
confidence: 99%